Analisis Evaluasi Kinerja Keuangan Dengan Metode ROI, RI, EVA Dan Dengan Pendekatan Desentralisasi Terhadap Suatu Perusahaan - Fauzi, Achmand; Atmono, Agung Apri; Salsabila, Hana; Tristiany, Kania Dwi; Mubarok, Rachel Haliza (OGZ Research & Publishing, 2024)
This research aims to analyze the evaluation of company financial performance by considering the Return on Investment (ROI), Residual Income (RI), Economic Value Added (EVA) methods, and the decentralized approach. This method is used for comprehensive and in-depth measurement of a company's financial performance. Comparisons are made between traditional methods, EVA, and the impact of decentralization to answer key questions about the influence of each method on financial performance evaluation.The research also discusses the challenges that companies may face in implementing ROI, RI, EVA, and decentralization methods, and provides suggestions for overcoming these obstacles. The aim of this research is to add to the literature on financial performance evaluation and strategic management, providing insight into the various factors that influence financial performance evaluation.Descriptive analysis was carried out with a quantitative approach using secondary data from notes, documents and reports from various sources. The research results show that the decentralized approach and the ROI, RI, and EVA methods are correlated with each other in evaluating company financial performance. Although decentralization may not be significant in evaluating financial performance, it can influence management performance, create added value, and assist decision making to improve financial and business performance.